Nonlinear multi-photon Absorption of Strong electromagnetic wave with electron-acoustic phonon scattering in infinite semi-parabolic Plus semi- inverse Squared Quantum Wells - Nguyen, Thu Huong; Bui Thi, Dung; Nguyen Cong Huy,; Nguyen Quang Son,; Nguyen, Quang Bau (Communications in Physics, 2025)
Theoretical study on the nonlinear absorption of a strong electromagnetic waves in infinite semi-parabolic plus semi-inverse Squared Quantum Wells (ISPPSISQW) by using quantum kinetic equations for electron in the case of electron-acoustic phonon scattering. Analytical expressions for the nonlinear multi-photon absorption coefficient in the ISPPSISQW are obtained for a specific GaAs/GaAsAl in the case off the absence and the case of the presence of an external magnetic field B. A second- order multi-photon process is included in the result. The dependence of the nonlinear multi-photon absorption coefficient on the intensity $(E_0)$ and the frequency $(Ω)$ of a strong electromagnetic wave, confinement frequency of ISPPSISQW $(Ω)$ and the temperature investigated. The numerical computations for a specific ISPPSISQW GaAs/GaAsAl show that the nonlinear multi-photon absorption coefficient decreases rapidly with increasing $ω_z$ or $Ω$ and the nonlinear multi-photon absorption coefficient increases rapidly $E_0$ or T. In the case of the presence of an external magnetic field B, numerical calculations indicate the occurrence of magneto-photon-phonon resonances when the resonance conditions are met. As the photon energy changes, the resonance peaks tend to increase with the increase in photon energy.